STRAITS OF MALACCA AS A KNOWLEDGE CORRIDOR: PERAN JALUR MARITIM DALAM MOBILITAS ULAMA DAN ILMU (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
The Straits of Malacca has historically functioned not only as a major international trade route but also as a meeting space of civilizations and a crucial corridor for the transmission of Islamic knowledge. This article aims to analyze the role of the Straits of Malacca as a knowledge corridor that facilitated the mobility of Muslim scholars, the circulation of Islamic texts, and the formation of intellectual networks connecting the Middle East, India, and the Malay-Indonesian world. Employing a qualitative historical approach based on literature review of maritime history, ulama biographies, manuscripts, and reputable journal articles, this study demonstrates that the Straits of Malacca served as an epistemic space enabling the integration of global and local Islamic scholarly traditions, particularly in the fields of jurisprudence, Sufism, Qur’anic exegesis, and Hadith. The mobility of scholars along this maritime route not only accelerated the process of Islamization but also shaped scholarly authority, Islamic educational curricula, and enduring intellectual traditions across coastal and inland regions of Southeast Asia. Thus, the Straits of Malacca should be understood not merely as an economic passage but as a strategic knowledge corridor in the formation of Islamic civilization and scholarly culture in the region.